Behavior of large-scale connections between circular concrete-filled steel tubular columns and H-section steel beams. Issue 2 (January 2020) - Yang, Yuanlong; Liu, Xianggang; Zhang, Jun; Liu, Jiepeng; Cheng, Wei
Three large-scale connections between circular concrete-filled steel tubular columns and H-section steel beams were tested. The specimens include one connection with T-shaped stiffeners under static load and two connections, respectively, with T-shaped stiffeners and diaphragms (including interior and exterior diaphragms) under cyclic loads. During the test, the experimental phenomena were observed. The static properties of strength and ductility are calculated for static connection based on load–displacement curves, while the seismic properties of strength, ductility, and energy dissipation are analyzed for seismic connections based on hysteretic load–displacement curves. Combining experimental phenomena, mechanical properties, and stress development, the beam-hinge failure mode can be identified for all specimens. The measured beam strengths of specimens are compared with those predicted by the current AISC-360, EC4, and GB 50017-2017 codes. The study results show that all connections are reliable. A finite element model, established and verified with the experimental results, is used to perform parametric analysis. Furthermore, design suggestions of T-shaped stiffeners and diaphragms are proposed based on a parametric analysis.